Analisis Laporan Keuangan Unit Pengelola Kegiatan Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan Dalam Pengukuran Profitabilitas - adi maulana Rachman; ismail ismail; parman parman (Musamus Journal of Economics Development, 2022)
ABSTRACT The title that the author proposes in this study is "Financial Statement Analysis in Measuring Profitability Levels in the Rural PNPM Mandiri Activity Management Unit, Cinangka District, Serang Regency". measuring the level of profitability in the PNPM Mandiri Rural Activity Management Unit, Cinangka District, Serang Regency. To discuss the formulation of the problem above, in this study the author uses a descriptive research method, namely a method that describes or solves problems faced in the present. With data collection techniques documentation, interviews, observations, and literature study. With analysis techniques and the ratio of operating profit to business assets, the ratio of the rate of return on investment, and the ratio of economic profitability. The result of this research is the analysis of profitability ratios for 2013 by 3%. So the results of the study can answer the question of research problems, namely that the analysis of financial statements can be used as a tool for management to determine the level of profitability in the PNPM Mandiri Rural Activity Management Unit, Cinangka District, Serang Regency. As for reducing the decrease in the profitability ratio of the PNPM Mandiri Rural Activity Management Unit, Cinangka District, Serang Regency, efforts are made to increase revenue and reduce costs so that an increase in profit is obtained. Keywords: financial statement analysis, profitability, PNPM Mandiri Rural